2012
DOI: 10.1002/crat.201200026
|View full text |Cite
|
Sign up to set email alerts
|

Optical and magnetic properties of Nd‐doped ZnO nanoparticles

Abstract: Nd‐doped ZnO nanoparticles with different concentration were synthesized by sol‐gel method. The structures, magnetic and optical properties of as‐synthesized nanorods were investigated. X‐ray diffraction (XRD) and x‐ray photoelectron spectroscopy (XPS) results demonstrated that Nd ions were incorporated into ZnO lattice; but Zn1‐xNdxO nanoparticles with Nd concentration of x = 0.05 showed Nd2O3 phase, so the saturation concentration of Nd in Zn1‐xNdxO is less than 5 at%. Vibrating sample magnetometer (VSM) mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 30 publications
8
16
0
Order By: Relevance
“…A newer LUMO is therefore formed which leads to a reduction of the band gap. Note that such decrease in the gap is in agreement with the red shift of the excitonic peak observed in photoluminescence measurements for Nd-doped ZnO [23,35] and in other transition metal doped ZnO films grown by spray and other techniques [12,[36][37][38].…”
Section: -P3supporting
confidence: 87%
See 2 more Smart Citations
“…A newer LUMO is therefore formed which leads to a reduction of the band gap. Note that such decrease in the gap is in agreement with the red shift of the excitonic peak observed in photoluminescence measurements for Nd-doped ZnO [23,35] and in other transition metal doped ZnO films grown by spray and other techniques [12,[36][37][38].…”
Section: -P3supporting
confidence: 87%
“…For larger Nd concentrations, the resistivity decreases again and the n-type character is reinforced (increase of the carrier concentration). This suggests that further doping does not lead to an increase of Nd ions in substitution of the Zn ions, but to the appearance of new defects (not necessarily optically active) and to spurious phases (such as Nd 2 O 3 which was reported in highly doped ZnO samples [35] that increase further the n-type conduction. These results are in agreement with both XRD and photoluminescence results.…”
Section: -P3mentioning
confidence: 81%
See 1 more Smart Citation
“…Nd (a lan− thanide) doped ZnO leads to a band gap narrowing although the dopant is in +3 state. Douyar et al [12] has reported that according to Zheng et al [32] Nd 4f electrons introduce new states close to the conduction band of ZnO. A newer LUMO is therefore formed which leads to a reduction of the band gap [12].…”
Section: Transmission and Optical Band Gapmentioning
confidence: 99%
“…Several methods for the synthesis of ZnO are reported in the literature, such as co-precipitation, ultrasonic radiation using precipitation, microwave irradiation, mechanical ball milling, solution combustion and microwave assisted solvothermal methods [12][13][14][15]. Among these methods, coprecipitation method attracts more attention due to its unique advantages including low cost, simple lab equipment, easy adjustment of dopant concentration and ability to produce large amount of nanoparticles (NPs) etc., In the present paper, a simple co-precipitation method was applied for the preparation of Nd doped ZnO NPs.…”
Section: Introductionmentioning
confidence: 99%